Newsletter no. 13 - International Commission on the History of Geological Sciences; Guntau, Martin (My University, 1979)
INHIGEO produces an annual publication that includes information on the commission's activities, national reports, book reviews, interviews and occasional historical articles.
Informationsbrief nr. 13
Keywords: Geology -- History -- Congresses